One dark night - Wheeler, Lisa, 1963-; Bates, Ivan (San Diego : Harcourt, 2003)
Mouse and Mole feel afraid one dark night crossing a mush-mucky swamp and a marsh-misty wood.
Keywords: Mice -- Fiction; Moles (Animals) -- Fiction; Fear -- Fiction; Bears -- Fiction; Friendship -- Fiction; Stories in rhyme